Tinjuan Kriminologi Penganiayaan dan Pemerkosaan oleh Anak Kandung terhadap Ibu Kandung di Kabupaten Manggarai Timur - Maria Febrianti Dia; Daud Dima Tallo; Rudepel Petrus Leo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study discusses the factors causing abuse and rape against biological mothers and the efforts to combat these crimes against women (biological mothers). The aim of the research is to identify the factors causing abuse and rape against biological mothers and to determine the efforts to combat abuse and rape against biological mothers in East Manggarai Regency. The research methodology used is empirical research, conducted directly in the field and carried out at the Indonesian National Police, East Manggarai Regency. The research results indicate that the factors causing abuse and rape by biological children against biological mothers are sexuality, mental health, moral factors of the perpetrators, economic factors, low education, and environmental factors. This study also shows that the efforts made by the East Manggarai Regency Police to combat abuse and rape against biological mothers include preventive and repressive measures.